What is in the drug packet?: access and use of non-prescribed poly-pharmaceutical packs (Yaa Chud) in the community in Thailand - Malee Sunpuwan; Sureeporn Punpuing; Wipaporn Jaruruengpaisan; John Kinsman; Heiman Wertheim (BMC Public Health, 2019)
Abstract Background ‘Yaa Chud’ is a non-prescribed poly-pharmaceutical pack containing several types of drugs, including antibiotics and steroids, which can be purchased over the counter in Thailand for self-medication. Although it is illegal, it is still available at some community outlets. This study aimed to understand access to and use of Yaa Chud at the community level in order to raise awareness on its usage and to provide policy recommendations to address the problem. Methods This study employed qualitative methods, including in-depth interviews with 18 drug suppliers and 16 community members, and six focus group discussions. It included inventories from 17 drug suppliers. Data were collected in selected communities of the Kanchanaburi Demographic Surveillance System, located in the western region of Thailand.Thematic analysis was based upon the Health Services Utilization Model and conducted using the Open Code qualitative software program. Results Overcrowding, long waiting times, and a perceived unwelcoming environment at public health-care service outlets were identified as factors that drive people into the private sector, where loose regulation of drug laws facilitates access and use of Yaa Chud. Migrants and older people were most likely to seek and use Yaa Chud, especially for mild illness. Availability, easy access through a user’s network, low cost, and perceived effectiveness were identified as factors that enable access and use of Yaa Chud. Conclusions Though illegal in Thailand, Yaa Chud is likely to remain available for self-medication by community members, due to the persisting demand by the elderly and migrant workers. There is an urgent need to replace these mixed medications with better choices. Safer Yaa Chud may be a preferred, first-line health-care option, which could help reduce congestion in the formal health-care setting. At the same time, enforcement of regulatory compliance needs to be continued in order to stop the supply of unsafe Yaa Chud.